Strategic Green HRM for Policy Development Toward Zero Emission Zones (ZEZ) in Higher Education Institutions - Resmiati, Eny Nuryani; Rahmat, Taufiq; Ardiansyah, Iwan (Program Studi Manajemen, Universitas Al Ghifari, 2023)
The transition toward Zero Emission Zones (ZEZ) in higher education institutions (HEIs) faces systemic challenges, particularly the underutilization of HRM as a strategic driver of sustainability. In many universities, HRM remains focused on administrative functions rather than catalyzing behavioral and institutional transformation aligned with climate goals. This study aims to develop a strategic Green HRM model to support policy development and operational change toward ZEZ implementation in HEIs.Using a Design Thinking approach comprising five stages—empathize, define, ideate, prototype, and test—the research explores current practices, identifies institutional barriers, and co-creates solutions across selected Indonesian universities. The findings reveal that integrating green job design, environmental training, eco-based performance indicators, and prophetic leadership significantly enhances staff engagement, reduces energy use, and promotes low-carbon innovation. Pilot testing demonstrates that digital platforms supporting HR-led emission monitoring and incentive structures can accelerate sustainability culture within academic settings.